(untitled) (Research, Society and Development, 2020)
The human papillomavirus (HPV) is responsible for one of the most common sexually transmitted diseases on the planet, about 80% of the currently active population has already been exposed to the virus. The man who is being the main link in the epidemiological chain, acts as the main carrier and vector of viruses, and the proliferation is done via sexual transmission. Objective: This study sought to analyze the scientific production in relation to the factors that influence the manifestation of HPV in men, considering the main forms of transmission, prevention, diagnosis and treatment. Methodology: The present study deals with an integrative literature review, with a qualitative approach, produced from January to April 2020, carried out in the databases: MEDLINE, LILACS and PUBMED. Articles published in the period from 2015 to 2020, articles in Portuguese and English and excluded articles and incomplete texts that did not coincide with the object of study were included. Results: an analysis of the publications allowed that, through this problem, it is important for Nursing to obtain practical and theoretical knowledge from what has already been published for safety and knowledge in order to be able to offer good assistance to a person infected with HPV. Conclusion: It is evident that the perception of health professionals should increase their knowledge, based on what has already been published about HPV infection in men and in society as a whole, as it is of great relevance, thus facilitating an approach to the theme in your daily appointments.